Government as a legal phenomenon - Ладиченко, Віктор Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The author considers the article in the state power as a complex, multidimensional and contradictory phenomenon. To some extent, science has not produced a single view of its concepts and principles. There is no generally accepted theory and holistic government, as government at all. Actual manifestations of this phenomenon continues, as rightly pointed Michel Foucault, remain somewhat mysterious, unknown, even demonic.